In Silico Evaluation of the Haplotype Diversity, Phylogenetic Variation and Population Structure of Human E. granulosus sensu stricto (G1 Genotype) Sequences - Selcuk, Muhammed Ahmed; Celik, Figen; Kesik, Harun Kaya; Kilinc, Seyma Gunyakti; Ahmed, Haroon; Jiang, Nan; Cao, Jianping (Mdpi, 2022)
Echinococcus granulosus sensu lato is the causative agent of cystic echinococcosis (CE), which is a neglected zoonotic disease with an important role in human morbidity. In this study, we aimed to investigate the haplotype diversity, genetic variation, population structure and phylogeny of human E. granulosus sensu stricto (s.s.) (G1 genotype) isolates submitted to GenBank from different parts of the world by sequencing the mitochondrial CO1 and ND1 genes. The sequences of the mt-CO1 (401 bp; n = 133) and mt-ND1 (407 bp; n = 140) genes were used to analyze the haplotype, polymorphism and phylogenetic of 273 E. granulosus s.s. (G1 genotype) isolates. Mutations were observed at 31 different points in the mt-CO1 gene sequences and at 100 different points in the mt-ND1 gene sequences. Furthermore, 34 haplotypes of the mt-CO1 sequences and 37 haplotypes of the mt-ND1 sequences were identified. Tajima's D, Fu's Fs, and Fu's LD values showed high negative values in both mt-CO1 and mt-ND1 gene fragments. The haplotype diversities in the sequences retrieved from GenBank in this study indicate that the genetic variation in human isolates of E. granulosus s.s. in western countries is higher than in eastern countries. This may be due to demographic expansions due to animal trades and natural selections.
Keywords: Echinococcus granulosus s.s.; G1 genotype; CO1; ND1; genetic variability